2013
DOI: 10.1152/ajpregu.00588.2012
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet changes the temporal profile of GLP-1 receptor-mediated hypophagia in rats

Abstract: Overconsumption of a high-fat diet promotes weight gain that can result in obesity and associated comorbidities, including Type 2 diabetes mellitus. Consumption of a high-fat diet also alters gut-brain communication. Glucagon-like peptide 1 (GLP-1) is an important gastrointestinal signal that modulates both short- and long-term energy balance and is integral in maintenance of glucose homeostasis. In the current study, we investigated whether high-fat diets (40% or 81% kcal from fat) modulated the ability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…In the current study, the food intake reduction effect persisted longer in HF-fed than chow-fed rats. Similar results have been demonstrated using both EX-4 and another long-acting GLP-1 analog liraglutide (42). A study by Hayes et al (26), however, showed that chow intake was decreased persistently and significantly throughout 7 days of EX-4 treatments.…”
Section: Discussionsupporting
confidence: 68%
“…In the current study, the food intake reduction effect persisted longer in HF-fed than chow-fed rats. Similar results have been demonstrated using both EX-4 and another long-acting GLP-1 analog liraglutide (42). A study by Hayes et al (26), however, showed that chow intake was decreased persistently and significantly throughout 7 days of EX-4 treatments.…”
Section: Discussionsupporting
confidence: 68%
“…Over the past two decades, it has become apparent that many of the currently available anti-diabetic drugs also act directly in the CNS (Table 1 and Figure 2). For instance, Liraglutide and Exenatide are known to act both in the periphery and at the level of the brain (Mul et al, 2013; Sisley et al, 2014). However, one recent study demonstrates that the glucose-lowering effects of Liraglutide are independent of GLP-1 receptor signaling in the brain (Sisley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that high fat diet-induced obesity impairs response to peripheral GLP-1, raising the possibility that increased body mass and adiposity could do the same for central GLP-1 (Mul et al, 2013; Williams et al, 2011). This was assessed in an experiment testing responsiveness to third ventricular infusion of Ex4 in animals fed a low fat chow diet and obese animals maintained on a high fat diet (Mul et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that high fat diet-induced obesity impairs response to peripheral GLP-1, raising the possibility that increased body mass and adiposity could do the same for central GLP-1 (Mul et al, 2013; Williams et al, 2011). This was assessed in an experiment testing responsiveness to third ventricular infusion of Ex4 in animals fed a low fat chow diet and obese animals maintained on a high fat diet (Mul et al, 2013). The effects of central Ex4 were equivalent across groups, indicating that responsiveness to central GLP-1R stimulation is not altered by increased body weight and adiposity, making it unlikely that these factors are responsible for the behavioral difference in our study of EB- and oil-treated OVX rats.…”
Section: Discussionmentioning
confidence: 99%